Modelo de gestión de continuidad en la infraestructura tecnológica de la Universidad Laica Eloy Alfaro de Manabí, basada en la norma ISO 22301 - Cano Montesdeoca, María Teresa (2019)
It is important to recognize the level of relevance that leads to the development of this research, whose main objective is to develop a Continuity Management Model in the Technological Infrastructure of the Eloy Alfaro University of Manabí, based on ISO 22301, for the purpose of improve the availability of services at the time of occurrence any eventuality. For the purpose of the research, the methodology by levels was used to comply with each of the proposed objectives. Initially, the current situation of the Central Computer Coordination Unit (UCCI) was determined and the main incidents were identified, which were assessed from very sensitive to not sensitive. With the Modal Analysis of Faults and Effects (AMFE) methodology, the probability and impact levels of the risks were reached, and as a complement to the research, the MAGERIT methodology was applied to identify the assets of the unit and the threats to which they may be exposed. Finally, the Continuity Management Model was elaborated, based on the following phases: Scope of the Business Continuity Plan (BCP), Risk Assessment, Business Impact Analysis (BIA), Recovery Strategies and Plan Development. It is concluded that the UCCI is exposed to critical risks caused by threats according to the analysis made with 59% of the level of criticality, so that the proposed model will significantly respond to possible incidents in order to continue operations in benefits of the University community.